Анализ электрокардиографических интервалов с помощью адаптивного метода нечеткой кластеризации данных - Чурюмова, И. Г. (ХНУРЭ, 2008)
The adaptive method of fuzzy clusterization for multiprocessing and serial processing of medicobiological data sets of a human organism is developed. Sort of the metrics is updated at clusterization of the medical data
Keywords: электрокардиография; medical data